The way of the bear [compact disc, unabridged] - Hillerman, Anne, 1949- (Hillerman, Tony. Leaphorn and Chee novel., 2023)
An unexpected death on a lonely road outside of Utah's Bears Ears National Park raises questions for Navajo Tribal Police officers Jim Chee and Bernadette Manuelito. Why would a seasoned outdoorsman and well-known paleontologist freeze to death within walking distance of his car? A second death brings more turmoil. Who is the unidentified man killed during a home invasion where nothing seems to have been taken? Why was he murdered? The Bears Ears area, at the edge of the Navajo Nation, is celebrated for its abundance of early human habitation sites and the discovery of unique fossils which revolutionized the scientific view of how early animals dealt with their changing world. For Chee and Bernie, the area glows with geological interest and spiritual insight. But their visit to this achingly beautiful place is disrupted by a current of unprecedented violence that sweeps them both into danger. An illicit business, a fossilized jaw bone, hints of witchcraft, and a mysterious disappearance during a blizzard and to the peril. It will take all of Manuelito's and Chee's experience, skill, and intuition to navigate the threats that arise beneath the twin buttes that give Bears Ears its name and to see justice served.